Case Study: The Application Of Suction Therapy For Airway Clearance In Patients With Pneumonia In The Intensive Care Uni Of Hospital X - Ellin Febriani; Maria Astrid (International Journal of Health Engineering and Technology, 2026)
Pneumonia remains one of the leading causes of respiratory disorders among critically ill patients admitted to the Intensive Care Unit (ICU). Pulmonary inflammation increases airway secretion production, leading to ineffective airway clearance, particularly in patients with decreased consciousness or artificial airways. Retained secretions may cause airway obstruction, impaired gas exchange, hypoxemia, and respiratory failure. Endotracheal suctioning is a nursing intervention aimed at maintaining airway patency by removing accumulated secretions. To describe the implementation of suctioning in managing ineffective airway clearance among patients with pneumonia admitted to the Intensive Care Unit of Hospital X. This study employed a descriptive case study design using the nursing process approach involving two patients diagnosed with pneumonia and ineffective airway clearance. Data were collected through family interviews, direct observation, physical examination, medical record review, and respiratory assessment before and after suctioning over two consecutive days. Respiratory rate, oxygen saturation, breath sounds, sputum volume, sputum characteristics, and patient responses were evaluated. The implementation of suctioning improved respiratory status in both patients. In the first patient, respiratory rate decreased from 24 to 22 breaths/minute, sputum production decreased from approximately 15 mL to 10 mL, rhonchi diminished, and oxygen saturation increased from 97% to 99%. In the second patient, respiratory rate decreased from 20 to 19 breaths/minute, sputum production decreased from approximately 10 mL to 5 mL, sputum became less viscous, rhonchi diminished, and oxygen saturation remained stable between 98% and 99%. Suctioning performed according to the standard operating procedure effectively maintains airway patency, reduces secretion retention, improves respiratory patterns, and enhances airway clearance in critically ill patients with pneumonia.